EFFECT OF MIXTURE EUCALYPTUS OIL AND MAGNETIC FIELDS ON DROPLETS COMBUSTION PALM OIL ON FLAME BEHAVIOURS AND FLUE GAS EMISSIONS - Perdana, Dony; Moh. Aris, Taufik (Journal of Renewable Energy and Mechanics, 2024)
This research has the purpose to determine and understand the role of repelling magnetic field and the variation of eucalyptus oil bio-additives on flame evolution and exhaust emissions in burning palm oil droplets. Presently, the requirement for energy is increasing, so people must look for alternative energy of fuels. Because the availability of fossil fuels cannot be renewed and their existence is increasingly depleting. This situation really forces us to develop vegetable oil as a new energy source, one of which is palm oil. This research method uses a direct testing method on palm oil which is given a variation of a mixture of eucalyptus oil bio-additives a droplet diameter of 0.3-0.4 mm at a thermocouple diameter of 0.12 mm with magnetic field strength of 10,000 Gauss and heated by heater component. This research has found that the role of repelling magnetic field N-N (north-north) and variations in eucalyptus oil bio-additives have a major influence on the evolution time of the flame. The mixture of 10% bio-additive produces the shortest flame time of 1600 milliseconds, the lowest flame height with a value of 5.74 mm, and the highest temperature of 894.25oC compared to other bio-additive variations. CO exhaust gas at 6% bio-additive produces the lowest value of 33 ppm while NOx exhaust gas at 10% bio-additive produces the lowest value of 545 ppm.